Production and trade of ICT from an EU perspective - Mahdi Ghodsi; Amat Adarov; Dimitrios Exadaktylos; Robert Stehrer; Roman Stöllinger (The Vienna Institute for International Economic Studies (wiiw), 2021)
The competitiveness of industries and countries is shaped more and more by technological advancement in the production and use of information and communications technology (ICT). This report considers the supply side of ICT goods and services. It studies the drivers of ICT production location and trade across countries with a focus on the relative position of the EU. The analyses clearly indicate that the EU must step up its efforts to accelerate the shift towards digital production and strengthening the ICT sector that produces the required technologies and services. In addition, from a trade policy perspective, a harmonised set of standards and regulatory framework is to be aimed at to minimise mismatches in technical specifications and requirements. This will lead to the diffusion of positive externalities and should allow for a smooth operation of the global value chains in these products.
Keywords: F14; O33; L11; L63; 330; information and communications technology; digitalisation; production patterns; trade patterns